Unges tanker om konfirmasjon: En studie blant 14-åringer forut for deres valg av ungdomsrite (Tidsskrift for Praktisk Teologi, 2020)
What meanings are attributed to Christian confirmation, among other confirmation rites in a changing religious landscape? The aim with the article is to gain new knowledge about the reasoning and conditions for choice of confirmation among 14-year-olds’ who have yet to decide which confirmation, if any, to choose. Data is collected through 10 focus group interviews with a total of 57 youth, and a statistical survey with 309 respondents distributed at five schools from the north to the south of Norway. The analysis shows that it is important for youth to emphasize their individual freedom when making the decision of confirmation. At the same time the family appears to be the most important social group in laying the premises for the youths’ decision. For some, the choice appears as an identity marker. Many show uncertainty concerning the choice of confirmation and how the rite is to be celebrated in the family. The Church is challenged by having to relate to a large variation of motivations and interests for participating in the confirmation rite among youth.